The Impact of Implementation of the Regulation of Minister of Marine and Fisheries Number 56 and 57 of 2014 to the Fishing Industry in Bitung, North Sulawesi, and Indonesia - Stanny S Rawung; Ficke H Rawung (AIBPM Publisher, 2018)
The fishing industry is the dominant driver of the Economy in Bitung. The major contribution of fishing industry to Bitung City made this city known by the term